2016
DOI: 10.18632/oncotarget.9533
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus stimulates pancreatic cancer growth and epithelial-mesenchymal transition-mediated metastasis via a p38 MAPK pathway

Abstract: Diabetes mellitus (DM) and its accompanying chronic inflammation promote tumor progression. p38 mitogen-activated protein kinase (MAPK) is an essential kinase for inflammation. The effects of p38 MAPK on epithelial-mesenchymal transition (EMT)-mediated diabetic pancreatic cancer metastasis remain unclear. Here, we demonstrate that p38 MAPK phosphorylation was significantly increased in pancreatic cancer cells treated with high glucose and in pancreatic tumors from diabetic animals. A p38 MAPK inhibitor signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
(25 reference statements)
1
33
0
Order By: Relevance
“…P38 MAPK is one of the important members of MAPK [52, 53]. Acting as an integration point for multiple biochemical signals, MAPK participates in a wide variety of cellular processes such as proliferation, differentiation and apoptosis [54-56]. The p38 MAPK pathway is known to play an important role in podocyte apoptosis [33, 57].…”
Section: Discussionmentioning
confidence: 99%
“…P38 MAPK is one of the important members of MAPK [52, 53]. Acting as an integration point for multiple biochemical signals, MAPK participates in a wide variety of cellular processes such as proliferation, differentiation and apoptosis [54-56]. The p38 MAPK pathway is known to play an important role in podocyte apoptosis [33, 57].…”
Section: Discussionmentioning
confidence: 99%
“…[23] Diabetes mellitus stimulates pancreatic cancer growth via the MAPK pathway. [24] High glucose increases glucose uptake and glycolytic activity, and stimulates cell proliferation through modulating the MAPK pathway. [25] Apart from PI3K/Akt pathway, MAPK pathway should be suspected to activate and greatly implicate in PTC development.…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, p38 MAPKs phosphorylate the serine/threonine residues of their substrates, which include several transcription factors as well as protein kinases (38). It has been reported that the activation and phosphorylation of p38 MAPK mediates the anticancer activity in numerous malignant cancers such as pancreatic (39) and gastric cancer (40), and head and neck carcinoma (41).…”
Section: Discussionmentioning
confidence: 99%